Pengaruh Pemupukan terhadap Panjang Cabang Kesambi (Schleichera oleosa (Lour.) Merr.) dan Produktivitas Lak di KPH Probolinggo - Noor Farikhah Haneda; Andi Sukendro; Yuni Fatmasari (Jurnal Silvikultur Tropika, 2020)
Kesambi (Schleichera oleosa (Lour.) Merr.) is a host plant that becomes priority in lac culture in Indonesia. Shellac is one of the non-timber forest product commodities, which is potential to be one of foreign exchange sources. World demand of shellac is increasing throughout the year so that the improvement of shellac productivity is required to fulfill the demand. One of the alternatives is implementing the fertilization due to host plant quality improvement considering that host plant is the source of nutrient of shellac. The activity of fertilization aims to understand the effect of fertilization dosage to the improvement of the branch length as well as productivity of shellac in KPH Probolinggo. The greatest average value of branch length during three and six months, respectively were 66.48 cm and 83.24 cm. While, the greatest average value of shellac productivity was 84.29 g. The treatment of fertilization in different dosage to the kesambi (Schleichera oleosa (Lour.) Merr.) was not give significant effect to the length of branch as well as shellac productivity. Keywords: fertilization, Kesambi, Shellac